A field screening technique for resistance of cowpea (Vigna unguiculata) to the pod-borer Maruca testulalis (Geyer) (Lepidoptera: Pyralidae) - Jackai, L.E.N. (1982)
A method for screening resistance of cowpea (Vigna unguiculata) to the legume pod-borer Maruca testulalis (Geyer) was developed. Several damage parameters were measured, including damage to stem, flowers, pods and seeds. Some of these parameters were assessed in more than one way. A decision was made at the end of the study as to which parameters were most appropriate for a field screening methodology. A plant resistance index, Ipr, was generated to aid in this decision. Based on this, it was concluded that flower, pod, and seed damage measurements provided the most important assessment of resistance to the borer. The larval population in the flowers showed marked differences in infestation levels between cultivars and is suggested as a means of comparing results in the future. Based on the methodology described, TVu 946 was the most resistant cowpea cultivar in every category of assessment. Five other cultivars were also selected for further evaluation as probable resistance donors: Kamboinse Local, TVu 1, VITA-5, TVx 3890–010F and VICAM-1/SP. The rationale behind the development of a field-screening methodology and some of its shortfalls are discussed.